2022
DOI: 10.1155/2022/8287192
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Infrared Combined with Methylcobalamin on the Vibratory Sensory Threshold and Nerve Conduction Velocity of the Lower Extremity in Patients with Diabetic Foot Treatment

Abstract: Objective. To investigate the effect of infrared combined with methylcobalamin on the vibratory sensory threshold and lower limb nerve conduction velocity of patients with diabetic foot. Methods. One hundred and six patients with diabetic foot in our hospital from February 2018 to December 2020 were enrolled and divided into the study and control groups. The patients in the control group were given methylcobalamin, and the patients in the research group were treated with infrared light on the basis of the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Yi Wang et al [26] used the KP-220 infrared therapy instrument (Power 32mW/cm², Wavelength 2-25um) combined with methylcobalamin irradiation for diabetic foot patients. The control group received daily methylcobalamin injections, while the study group underwent infrared therapy in addition to the standard treatment for 4 weeks.…”
Section: Infrared Lightmentioning
confidence: 99%
“…Yi Wang et al [26] used the KP-220 infrared therapy instrument (Power 32mW/cm², Wavelength 2-25um) combined with methylcobalamin irradiation for diabetic foot patients. The control group received daily methylcobalamin injections, while the study group underwent infrared therapy in addition to the standard treatment for 4 weeks.…”
Section: Infrared Lightmentioning
confidence: 99%
“…Recombinant bovine basic Fibroblast Growth Factor (rb-bFGF) gel can repair wounds, promote tissue regeneration and improve local microcirculation, thus accelerating wound healing [7] . Previous studies believed that during the pathological process, the lower extremity blood vessels of DFU patients would be in chronic inflammatory state and there would be secretion of inflammatory factors [8] . High-sensitivity C-Reactive Protein (hs-CRP) is an acute reactive protein that is strongly associated with the collective inflammatory response [9] .…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%